UNDERSTANDING DIGITAL MARKETING AND PUBLIC RELATIONS STRATEGIES IN BUILDING CONSUMER LOYALTY IN COFFEE SHOPS IN KENDARI CITY - Muh. Husriadi; Maulidia Berlianti; Aini Ashary (INJOSEDU: International Journal of Social and Education, 2026)
The development of digital marketing and public relations have changed the way coffee Coffee shops build relationships with consumers, especially amidst increasingly fierce business competition in Kendari City. However, few studies have explored how consumers understand and interpret these two strategies in depth to foster loyalty. This study aims to analyze the experiences and interpretations of coffee shop managers and consumers. shops in Kendari City regarding digital marketing and public strategies relationships in building customer loyalty. This study used a qualitative approach with a phenomenological design. Data were collected through observation, in-depth interviews, and documentation with managers and active coffee consumers. A shop in Kendari City was then analyzed using the Miles and Huberman model. The results showed that consumer loyalty is formed through the intensity of social media use, the quality of visual content, honesty of communication, speed of response, comfortable atmosphere, friendly service, and consistency of experience between digital promotions and real-life conditions. These findings confirm that loyalty is determined not only by product quality but also by trust, emotional experiences, and ongoing relationships between businesses and customers. The implications of this research provide a practical basis for coffee shop to develop a more authentic, responsive, and consumer experience-oriented communication strategy.